2022
DOI: 10.14393/sn-v34-2022-62940
|View full text |Cite
|
Sign up to set email alerts
|

Indicadores de Qualidade do Solo em Sistemas Agroecológicos no Cerrado Mineiro

Abstract: A qualidade do solo é a sua capacidade de funcionar dentro dos limites do ecossistema e do uso da terra para assegurar a produtividade biológica, preservar a qualidade ambiental e promover a saúde dos vegetais e dos animais. Assim, o objetivo deste trabalho foi selecionar indicadores de qualidade de solo sensíveis às diferentes práticas agrícolas adotadas em áreas de sistemas agroecológicos na região do Cerrado Mineiro. As amostras de solos foram coletadas na camada de 0 a 20 cm, no final do período de seca, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…This material, which contains immobilized nutrients in biomass, undergoes progressive decomposition, leading to the release of these elements Simultaneously, as tree plants grow and the system's complexity increases, there is also a progressive enhancement in the richness and diversity of multifunctional soil organismo. This microrganisms are responsible for decomposition and chemical elements remobilization in soil pro le (Odum, 1988;Gliessmann, 2007;Notaro et al, 2014;Rocha et al, 2022). Examples of these ecological interactions include mycorrhizae, symbioses, and other types of mutualistic ecological relationships (Notaro et al, 2014;Dobo et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…This material, which contains immobilized nutrients in biomass, undergoes progressive decomposition, leading to the release of these elements Simultaneously, as tree plants grow and the system's complexity increases, there is also a progressive enhancement in the richness and diversity of multifunctional soil organismo. This microrganisms are responsible for decomposition and chemical elements remobilization in soil pro le (Odum, 1988;Gliessmann, 2007;Notaro et al, 2014;Rocha et al, 2022). Examples of these ecological interactions include mycorrhizae, symbioses, and other types of mutualistic ecological relationships (Notaro et al, 2014;Dobo et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the availability of energy and nutrient resources and the limited oxidation of soil organic carbon, favoured by the prevalence of soil microorganisms, likely contributed to this observed enhancement. Koné et al [57] reported that soil microorganisms that in turn may improve biological activity in the rhizosphere include more plants with extensive rooting systems and more well-spread root hairs [58], and these characteristics are found to contribute to the exudation of vast amounts of organic compounds and consequently promote an increase in SMBC and SMBN [59]. These results are supported by Chaudhari et al (2020), who observed the combination of zero tillage + residue incorporation with inter-cultivation (IC) + hand weeding (HW) at 15, 30 and 45 DAS as the most suitable strategy for sustaining the greatest soil microbial biomass.…”
Section: Soil Microbial Activitymentioning
confidence: 99%
“…Additionally, the availability of energy and nutrient resources and the limited oxidation of soil organic carbon, favored by the prevalence of soil microorganisms, likely contributed to this observed enhancement. Koné et al [57] had also discovered that soil microorganisms which in turn may improve biological activity in the rhizosphere are higher plants with extensive rooting system and well-spread root hairs [58], and those characteristics are found to yield in the exudation of vast amounts of organic compounds and consequently promote a rise in SMBC and SMBN [59]. These Hazarika et al…”
Section: Soil Microbial Activitymentioning
confidence: 99%